Open versus Laparoscopic Inguinal Hernioplasty - Outcome Correlation - Ahmed, Akhter; Chowdhury, Salma Yesmin; Rahman, Md Mustafizur; Shimu, Farhana; Shahriar, Shaon; Mohammad, Din (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Repair of inguinal hernias in men is a common surgical procedure, but the most effective surgical technique is still in debate. Methods: We randomly assigned men with inguinal hernias at Mitford Hospital surgery, ward to either open mesh or laparoscopic mesh repair. The primary aim was to detect recurrence of hernias in both groups at 6 month. Secondary aims were to detect complications and patient compliance. Results: of the 70 patients who were randomly assigned to one of the two procedures, 62 underwent operation; 6 month follow-up was completed in 55 (78.6%). Recurrences were only one in the laparoscopic group (3.6%) and 1 in the open group (3.7%). The rate of complications was lower in the laparoscopic-surgery group than in the open-surgery group (17.6% vs. 27%). The laparoscopic- surgery group had less pain initially than the open-surgery group on the day of surgery (difference in mean score on a visual-analogue scale, 10.2 mm; 95 percent confidence interval, 4.8 to 15.6) and at two weeks (6.1 mm; 95 percent confidence interval, 1.7 to 10.5) and returned to normal activities earlier (adjusted hazard ratio for a shorter time to return to normal activities, 1.2; 95% confidence interval, 1.1 to 1.3). Hospital stay was shorter in laparoscopic group (2.6 days vs 3.2 days). Patients satisfaction with surgery was 95% in the laparoscopic group and 87% in open group. Nenety six laparoscopic and 87% of open surgery patients perceived that they were healthy after surgery. Total treatment cost was more in laparoscopic group. Conclusions: The laparoscopic technique is superior to the open technique for mesh repair of primary hernias. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 3-7